Binding of [3H] dihydroetorphine to opioid receptors in rat brain membrane - Wang Dan-Xin; Qin Bo-Yi (Acta Pharmacologica Sinica, 2016)
AIM: To study the binding characteristics of dihydroetorphine (DHE) to opioid receptors. METHODS: The binding of [3H] DHE to rat brain membrane opioid receptors was observed by radioligand binding study. RESULTS: Saturation study showed the binding of [3H] DHE to rat brain membrane presented a single high-affinity class of binding sites with Kd = 0.19 nmol.L-1 and Bmax = 115 pmol/g protein. Kinetics study showed the association rate of [3H] DHE to opioid receptor was very rapid and dissociation very slow. NaCl 100 mmol.L-1 + guanosine triphosphate (GTP) 50 mumol.L-1 inhibited the binding of [3H] DHE and made Kd increase to 7.87 nmol.L-1, without effect on Bmax. Competitive inhibition of agonists and antagonists indicated that the affinity of [3H]DHE to mu opioid receptor was higher than to delta and kappa opioid receptors. CONCLUSION: DHE is a selective agonist of mu opioid receptors.